Effect of Different Isolation Methods on DNA Quality of Snakehead Fish (Ophiocephalus sp.) - Putriana Sari Sirait; Septiana Sulistiawati (Universitas Muhammadiyah Palembang, 2023)
Differences in snakehead fish species can be detected through several markers, including DNA banding patterns. Isolation to obtain high-quality DNA is one of the basic rules that must be met in molecular studies, especially in DNA fingerprinting. DNA isolation methods can be done conventionally with CTAB (Cationic Hexadecyl Trimethyl Ammonium Bromide) or by using kits that have been provided by several companies to facilitate DNA isolation such as Qiagen and Thermoscientific. Therefore, it is necessary to compare the results of DNA isolation from various isolation methods so as to produce good DNA extraction. The results showed that the CTAB method was the best method. This is evidenced by the use of 2% CTAB as an extraction buffer has been able to break down cells and produce good quality DNA indicated by the presence of genomic DNA bands that match the target and have a high level of effectiveness.